Novel endophytic pestalotioid species associated with Itea in Thailand - Monkai, Jutamart; Phookamsak, Rungtiwa; Bhat, Darbhe Jayarama; Ei, Toe Swe Zin; Xu, Jianchu; Lumyong, Saisamorn (Frontiers in Cellular and Infection Microbiology, 2025)
Endophytic fungi are a well-known fascinating host-associated fungal group that can enhance plant growth and fitness by producing various bioactive secondary metabolites. They are an excellent source of industrial enzymes for potential secondary metabolite synthesis, which is useful in green agriculture, biotechnology, and pharmaceuticals. Itea is a valuable plant genus since it naturally contains rare sugar; however, endophytic fungi associated in this host have not yet been documented. In the present study, 11 strains of endophytic fungi were isolated and primarily identified as pestalotioid taxa based on morphological characteristics exhibited in vitro. Eleven strains of Pestalotiopsis-like taxa were isolated from the healthy leaves, stems, and roots of Itea japonica and I. riparia from Chiang Mai Province, Thailand. Species delimitation was based on morphology, multiloci phylogeny of a concatenated ITS, tub2, and tef1-α sequence data, and nucleotide polymorphism analyses. Neopestalotiopsis iteae and Pseudopestalotiopsis iteae are proposed as new species on I. japonica and I. riparia, respectively. Neopestalotiopsis chrysea, N. haikouensis, and Pestalotiopsis jinchanghensis are described as new records on I. riparia. Owing to the conspecific relationship based on multiloci phylogeny and identically nucleotide pairwise comparison of sufficient gene regions, several species are synonymized including Neopestalotiopsis cercidicola and N. terricola as N. haikouensis, N. umbrinospora as N. chrysea, and Pestalotiopsis zhaoqingensis as P. jinchanghensis. The updated phylogenetic trees, nucleotide comparisons, and morphological descriptions are herein provided and discussed for the taxonomic placements of these new species and records. This study is the first to investigate Itea endophytes in Thailand, and it reveals the intra- and interspecific relationships of pestalotioid species, which need to be further reevaluated because of ambiguous taxa.